Mapping shoreline changes due land reclamation using Landsat TM data - Sekon, Jamaah (2017)
Remote sensing sources very useful to capture continuous, repeatedly and recently data. Change detection technique using various type of satellite images in Remote Sensing have been using frequently and continuously previously. Edge change detection used is very sensitive to detect linear feature such as shoreline. Mapping shoreline changes due to only coastal reclamation for urban development purposes are using edge change detection technique in Envi 5.0 software and ArcGIS 10.2 for develop the databases. In order to mapping this changes, images pre-processing, filtering option until feature extraction stage will been used. Geographical Information System (GIS) as a tool for data input either spatial or attribute, data management, data display and manipulation. Therefore, both Remote Sensing and GIS known as a powerful approach to gather new information from primer to secondary data. New information will be tested by statistical of filtering and feature extraction technique and accuracy of Ground Control (GC) distortions. This testing will be produced very accurate of coastal changes area and shoreline changes due to coastal reclamation for urban development purposes.